Reduction in Kv Current Enhances the Temporal Dispersion of the Action Potential in Diabetic Myocytes: Insights From a Novel Repolarization Algorithm - Marianna Meo; Olivier Meste; Sergio Signore; Andrea Sorrentino; Antonio Cannata; Yu Zhou; Alex Matsuda; Marco Luciani; Ramaswamy Kannappan; Polina Goichberg; Annarosa Leri; Piero Anversa; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundDiabetes is associated with prolongation of the QT interval of the electrocardiogram and enhanced dispersion of ventricular repolarization, factors that, together with atherosclerosis and myocardial ischemia, may promote the occurrence of electrical disorders. Thus, we tested the possibility that alterations in transmembrane ionic currents reduce the repolarization reserve of myocytes, leading to action potential (AP) prolongation and enhanced beat‐to‐beat variability of repolarization. Methods and ResultsDiabetes was induced in mice with streptozotocin (STZ), and effects of hyperglycemia on electrical properties of whole heart and myocytes were studied with respect to an untreated control group (Ctrl) using electrocardiographic recordings in vivo, ex vivo perfused hearts, and single‐cell patch‐clamp analysis. Additionally, a newly developed algorithm was introduced to obtain detailed information of the impact of high glucose on AP profile. Compared to Ctrl, hyperglycemia in STZ‐treated animals was coupled with prolongation of the QT interval, enhanced temporal dispersion of electrical recovery, and susceptibility to ventricular arrhythmias, defects observed, in part, in the Akita mutant mouse model of type I diabetes. AP was prolonged and beat‐to‐beat variability of repolarization was enhanced in diabetic myocytes, with respect to Ctrl cells. Density of Kv K+ and L‐type Ca2+ currents were decreased in STZ myocytes, in comparison to cells from normoglycemic mice. Pharmacological reduction of Kv currents in Ctrl cells lengthened AP duration and increased temporal dispersion of repolarization, reiterating features identified in diabetic myocytes. ConclusionsReductions in the repolarizing K+ currents may contribute to electrical disturbances of the diabetic heart.